If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -4(2x + -1) = 45 + -4x Reorder the terms: 9 + -4(-1 + 2x) = 45 + -4x 9 + (-1 * -4 + 2x * -4) = 45 + -4x 9 + (4 + -8x) = 45 + -4x Combine like terms: 9 + 4 = 13 13 + -8x = 45 + -4x Solving 13 + -8x = 45 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 13 + -8x + 4x = 45 + -4x + 4x Combine like terms: -8x + 4x = -4x 13 + -4x = 45 + -4x + 4x Combine like terms: -4x + 4x = 0 13 + -4x = 45 + 0 13 + -4x = 45 Add '-13' to each side of the equation. 13 + -13 + -4x = 45 + -13 Combine like terms: 13 + -13 = 0 0 + -4x = 45 + -13 -4x = 45 + -13 Combine like terms: 45 + -13 = 32 -4x = 32 Divide each side by '-4'. x = -8 Simplifying x = -8
| (-3-7)+(4+7)= | | -152=4(-8+5m) | | b/9=a | | b/9=8 | | 38n+1=25 | | 3=-4/w-7 | | 3(-5a+9)-2(4a+6)= | | 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 | | 16Y-7y=500 | | 4x-3+0=-3x-4 | | ((12k^2h)-(3kh^2))/3kh | | 0.25(8-4p)+2p=12 | | 2x+19y=300 | | 60=x+71 | | -3(6-8n)=-138 | | 35-6x=13+5x |